Psychoanalysis and architecture theory. On the interdisciplinary approach in art theory - Razgulina, Maria V. (Actual Problems of Theory and History of Art, 2012)
The article is dedicated to the problem of using psychoanalysis methods in art theory involving interdisciplinary approach. The research is based on John Hendrix̓ monograph “Architecture and psychoanalysis. Peter Eisenman and Jacques Lacan”. This methodological approach is required here because the architecture of Peter Eisenman contains conceptual structures of psychoanalysis.